Management of DDI Ujung Lare Islamic Boarding School in Parepare City in Fostering Students - Nursan Nursan; Abd. Rahim Arsyad (Jurnal Kajian Manajemen Dakwah, 2022)
This study focuses on the Management of Pondok Pesantren DDI Ujung Lare in the City of Parepare in the Guidance of Santri, the purpose of this study is to determine the Management of Pondok Pesantren in the Guidance of Santri and the Application of Management in the DDI Pesantren of Ujung Lare, City of Parepare. This study uses a qualitative descriptive approach, namely research that produces data in the form of words and actions both orally and in writing.Collecting data using observation, interviews, and documentation. Data analysis processing techniques used are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the management of the Islamic boarding school in fostering students is good enough in fostering students because most students have felt satisfaction in the guidance provided at the Ujung Lare Islamic Boarding School, because the leader who is the top management gives an instruction to his subordinates who consisting of a leadership secretary, santri coaches, cottage staff, principals of Aliyah, Tsanawiyah and Ibtidaiyah schools according to their respective expertise in fostering students well and the existence of a system of rules in which the rules are obeyed by students so that it can make it easier for coaches to foster students.